Pelatihan Rekayasa Media Tanam dan Pemupukan Bibit Anggrek kepada Saka Taruna Bumi dan Santri Pondok Pesantren Mabdaul ‘Uluum Kota Tasikmalaya - Tini Sudartini; Adam Saepudin; Ida Hodijah (Jurnal Pengabdian Siliwangi, 2019)
Saka Taruna Bumi (Mitra activit 1) is the place for Pramuka to increase and develop the leadearship, knowledgeexperiences skill and proficiencies of its members. Thus they can conduc real activity abd productively and usefull in supporting agrycultural development program., includes 5 tasks :agricultural foodplant tasks, crop plantation tasks, fisheri tasks, veterinary tasks and horticultural plant tasks.  Those while tasks have not yet fully conducted.  Pondok Pesantren . Mabdaul ‘Uluum  (Mitra activity 2) lies in Mulyasari villages Tamansari district Tasikmalaya city.  Its student old about 13 years until 22 years.  The student bedide learn Islam religion understanding , also complete enhancement of knowledge and skill for instance  entrepreuneurship awareness, although it is an extra curriculum.  Actually  entrepreneurship knowledges student have already programed, but really still in foreword, because of various problem .  The problem comes from student its self who poor in knowledge and skill, minimal budget problem and minimal facilities.  Training for increasing productively knowledge and skill can be the  productively entrepreneurship, action such as training plant medium and fertilizing modification on orchid . Orchid cultivation need minimal areal and can be conducted  in the area of Mitra Activity 1 and 2,  on free time.Orchid plant is comersialized in three phase: seedling, young individu pot and orchid flower pot.The problem of Entrepreneurship program that still faced in Mitra Activity 1 and 2   were : 1). Mitra Activity 1 and 2  have not yet be familiar with orchid plant type 2). Mitra Activity 1 and 2   poor in knowledge and skill orchid cultivation. 3. Mitra Activity 1 and 2  are  poorly in how to marketing orhid commodity.  To solve those problems, IbBM skim program, about knowledge in  orchid agribusiness and  marketing; orchid biotechnology,propagation and type of orchid,practising growth  orchid in medium various type , maintance through fertilizing, plant protection and plant storage was already succesfull implemented in mitra Saka Taruna Bumi and Santri Pondok Pesantren Mabdaul ‘Uluum  Tasikmalaya city